Emergency Management of Bleeding Esophageal Varices: Drugs, Bands or Sleep? - Brian M Yan; Samuel S Lee (Canadian Journal of Gastroenterology)
Variceal bleeding is a severe complication of cirrhosis leading to significant morbidity and mortality. Treatment of acute variceal bleeding has improved dramatically since the era of the mechanical balloon tamponade. These advances include endoscopic band ligation or sclerotherapy, and vasoactive pharmacological options such as somatostatin, octreotide, vasopressin and terlipressin. Evidence from a multitude of clinical trials and meta-analyses comparing endoscopic and pharmacological treatments suggests near equivalence in efficacy for initial hemostasis, mortality and rate of rebleeding. This raises the question of whether on-call gastroenterologists should be performing emergency endoscopic treatment in the middle of the night or start pharmacological treatment and delay endoscopy until optimal patient and working conditions the next morning. The present review analyzes the available comparative data between endoscopic and pharmacological treatment options. Although the literature cannot yet definitively answer the question posed, the authors suggest that delaying endoscopic treatment until the next morning may be the most reasonable practical approach.